Electrochemotherapy for advanced cutaneous angiosarcoma: A European register-based cohort study from the International Network for Sharing Practices of electrochemotherapy (InspECT). (December 2019) - Campana, Luca G.; Kis, Erika; Bottyán, Krisztina; Orlando, Antonio; de Terlizzi, Francesca; Mitsala, Grammatiki; Careri, Rosanna; Curatolo, Pietro; Snoj, Marko; Sersa, Gregor; Valpione, Sara; Quaglino, Pietro; et al.
Abstract: Background: Cutaneous angiosarcoma (cAS) is a highly aggressive malignancy that challenges the radicality of surgical treatment. Electrochemotherapy (ECT), a skin-directed treatment based on cytotoxic chemotherapy combined with local electric pulses, may be an intraoperative adjunct and a new opportunity in the therapeutic strategy. This cohort study reports the experience with ECT as an option. Methods: Data on patients with locally-advanced/metastatic cAS who underwent ECT between October 2013 and October 2018 at eight European centres were prospectively submitted to the InspECT (International network for sharing practices of ECT) register. Patients received therapy according to the European Standard Operating Procedures of ECT (ESOPE). Treatment feasibility was assessed based on tumour coverage with electrodes and recorded tissue current; treatment toxicity and tumour response were graded according to CTCAE v5.0 and RECIST v1.1 criteria, respectively; patient-reported outcomes (PRO) were evaluated using a visual analogue score (VAS) for pain, acceptance of retreatment and the EQ-5D questionnaire. Results: We enrolled 20 patients with advanced cAS in the scalp/face (n = 7), breast/trunk (n = 10) or limbs (n = 3). Target tumours (n = 51) had a median size of 2.3 cm (range, 1–20). We administered 24 ECT courses using 1–4 cm treatment safety margin around tumours. In five patients, ECT was combined/sequenced with surgery. Median tissue current was 3 A (range, 1.5–10), tumour margins coverage rate was 75% (15/20 patients). The objective response rate (ORR) was 80% (complete, 40%). Grade-3 toxicity included skin ulceration (15%) and pain (10%), with no significant change of PRO scores. Bleeding control was achieved in 13/14 patients with ulcerated tumours. With a median overall survival of 12.5 months, the local progression-free survival (LPFS) was 10.9 months. Conclusion: ECT produces sustained response rate with minimal side effects and should be considered an option for advanced cAS. Palliative benefits include patient tolerability, local haemostasis and durable local control. Definition of optimal timing, treatment safety margins and combination with surgery need further investigation. Graphical abstract: Image 1 Highlights: Radical resection is a challenge in advanced cutaneous angiosarcoma. Electrochemotherapy may be avaluable alternative or an adjunct to surgical strategy Complete response was reported in 8/20 patients in the InspECT register. The procedure was tolerable, with mild and reversible skin toxicity. Benefits included durable control on local tumour growth and bleeding.